2008
DOI: 10.1001/archfaci.10.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cosmetic Facial Surgery on Satisfaction With Appearance and Quality of Life

Abstract: To assess perioperative quality-of-life (QOL) changes in a facial plastic surgery patient population and to ascertain factors determinative of QOL changes. A notable paucity of objective scientific measurements of QOL exists within the facial plastic surgery literature.Methods: A 3-year prospective cohort study. The patient population, which comprised a consecutive series of patients 16 years or older, undergoing cosmetic nasal or facial surgery, was obtained from the senior author's (P.A.A.) private surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 14 publications
10
46
0
6
Order By: Relevance
“…A study by Hellings et al [26] indicated that rhinoplasty caused an increase in personal satisfaction. Similar to our study, a study by Litner et al [27] showed that rhinoplasty caused an increase in QOL.…”
Section: Discussionsupporting
confidence: 92%
“…A study by Hellings et al [26] indicated that rhinoplasty caused an increase in personal satisfaction. Similar to our study, a study by Litner et al [27] showed that rhinoplasty caused an increase in QOL.…”
Section: Discussionsupporting
confidence: 92%
“…One of the main success factors for surgery is the patient's satisfaction after the procedure. Recently, many review papers were carried out in order to select a tool capable of measuring and analyzing patient satisfaction in the post-op [13][14][15][16][17][18][19][20][21][22] . Alssarraf et al created and validated the ROE Questionnaire, a tool of easy and fast application, useful to assess different types of patients, approaches and surgical techniques 17,19,22 .…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of the intervention's final result was not very much studied under the patient's viewpoint, and such analysis is very important because patient satisfaction is the prevailing factor for surgical success [13][14][15][16][17] . In the recent decade, numerous have been the papers published in order to validate a reliable questionnaire to be employed in patients submitted to cosmetic surgery, with the goal of measuring patient satisfaction after the procedure [17][18][19][20][21][22] . Some instruments, such as questionnaires, which assess quality of life and self-image have become a gold standard and came to replace the simplistic way used to ask the patient whether or not he/she had noticed any improvement after surgery 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the last decade has seen an explosion of interest in tools for assessing quality of life as a surrogate measure of overall benefit from health interventions. This interest has extended recently to the cosmetic surgery population (13). A series of measures related to health QOL (quality of life) is now available.…”
Section: Discussionmentioning
confidence: 99%